Tabish Khair’s ’Just Another Jihadi Jane’: Transgressing to Transform and Transcend - Bajraktarević, Faruk (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper discusses Tabish Khair’s novel Just Another Jihadi Jane as a literary contribution to re-examining established neo-orientalist notions of female agency in militant organizations like the Islamic State. Drawing from a number of theoretical analyses of the insufficiency of normative approaches to the concept of female agency cast within binary frames, I argue that Just Another Jihadi Jane resists widely spread views of female jihadists as either agential heroines or agentless victims of propagandist manipulation, promoting a non-binary view of female agency by narratively interpreting its contextualized specific manifestations. The principal importance of this novel thus lies in Khair’s deconstructive takes on a number of established dichotomies informing generic gendered interpretations of female participation in militant jihadist organizations and self-sacrifice in suicide attacks as outcomes of manipulation or pathologic nihilism, depicting a range of transgressive practices, including the final suicide attack – performed by, as it turns out, not just another Jihadi Jane - as not only contextually determined acts of quiet and loud resistance to sovereign power but also altruistic acts of instrumentalizing death and destruction to transfer vitality to others and professing a transcendental order negated by the brutality of its self-proclaimed emissaries.